Uniform Susceptibility of Various Strains of Coccidioides immitis to Amphotericin B - Collins, M. S. (1977)
The susceptibility of 12 strains of Coccidioides immitis to amphotericin B (amB) was studied in vitro and in vivo. The minimal inhibitory concentration (MIC) of the mycelial phase of these strains was 0.078 to 0.16 μg/ml after 3 days of incubation, but by 15 days all strains were inhibited by 2.5 μg/ml. Mice infected intraperitoneally with these strains were sucessfully treated with 0.5 mg of amB per kg per day. These strains included several studied by others and which reportedly varied widely in susceptibility (MIC from 0.24 to 24.01 μg/ml) to amB. Four of these strains representing this putative broad range of susceptibility were used to infect mice intranasally. Regardless of infecting strain, mice were sucessfully treated with 0.38, 0.75, and 1.5 mg/kg, but 0.19 mg/kg was only partially effective. Thus, in vivo as well as in vitro there was a uniform response of C. immitis strains to amB.